Outcomes of Proximal Femoral Locking-plate Fixation for Pathological Fractures of the Proximal Femur - Riansuwan, Kongkhet; Jivasomboonkul, Somkiat; Phimolsarnti, Rapin; Chandhanayingyong, Chandhanarat; Asavamongkolkul, Apichat (Siriraj Medical Journal, 2021)
Objective: To study the treatment outcomes of proximal femoral locking-plate fixation of pathological fractures of the proximal femur relative to clinical results, implant failure, and surgical complications. Materials and Methods: From 2007 to 2018, 17 patients (18 femurs) with a diagnosis of impending or existing pathological fracture of the proximal femur were treated with proximal femoral locking-plate fixation. Data collected included operative duration, estimated blood loss, ambulatory status, hardware failure events, and postoperative complications. Results: Of the 18 femurs that were included, 13 were existing pathological fractures and 5 were impending fractures. The mean age of patients was 53.7 years (range: 28-89), and 12 of them were female. The mean follow-up was 11.3 months (range: 1-67). Ten of 17 patients (62.5%) had progressive lung disease from pulmonary metastasis or from lung primary. No patient developed oxygen desaturation or cardiac arrest during the intraoperative or postoperative period. Thirteen of 17 patients (76.5%) could walk with or without an assistive device at the time of final follow-up. Two patients required close postoperative monitoring in the intensive care unit due to poor preoperative status, and both of those patients died within one month after surgery from other medical problems. No hardware failure occurred. Conclusion: For pathological fracture of the proximal femur, proximal femoral locking-plate fixation is a treatment option that results in fewer perioperative and postoperative cardiopulmonary events and surgical complications. Most patients can ambulate with or without an assistive device at the final follow-up.